Pengaruh Latihan Miring Kanan Miring Kiri terhadap Peningkatan Peristaltik Usus pada Pasien Operasi Laparotomi: Scoping Review - Suriadi Haryanto; Rafita Ofti Sefilena (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Postoperative paralytic ileus is a common complication after laparotomy surgery that can delay recovery and prolong hospital stays. Side-to-side turning exercises, as part of early mobilization, are frequently applied in nursing practice to stimulate intestinal motility, yet specific evidence mapping regarding this intervention remains limited. Objective: This study aims to map the scientific evidence concerning the effect of side-to-side turning exercises on increasing intestinal peristalsis in post-laparotomy patients. Methods: This scoping review follows the JBI methodological framework and PRISMA-ScR guidelines. A literature search was conducted on PubMed, ScienceDirect, and Google Scholar, with inclusion criteria for primary studies testing lateral positioning interventions in adult laparotomy patients and measuring intestinal peristalsis outcomes. Results: Five selected articles demonstrated that side-to-side turning exercises significantly (p < 0.05) accelerate the recovery of intestinal peristalsis. The most effective initiation of the exercise was found between 6 and 12 hours post-surgery, with an average duration of 30 minutes. While effective as an initial mechanical stimulation, this intervention is often combined with other mobilization activities, making it difficult to isolate its single effect. Conclusion: Side-to-side turning exercises are an effective and safe independent nursing intervention for improving intestinal peristalsis. Standardization of protocols regarding the optimal duration of lateral positioning is needed to strengthen clinical evidence in surgical nursing care.